Advancements in the Analytical Quantification of Nitroxidative Stress Biomarker 3-Nitrotyrosine in Biological Matrices. (3rd May 2020) - Bandookwala, Maria; Thakkar, Disha; Sengupta, Pinaki
Abstract: Dysfunction of the antioxidant system or mutations in the gene may result in the elevated production of certain biomarkers. 3-nitrotyrosine (3-NT) is one such promising biomarker of oxidative stress formed due to nitration of protein bound and free tyrosine residues. It has a significant potential to be exploited for the early diagnosis of diseases. There are a plethora of studies in which 3-NT has been utilized from the pharmacological perspective. However, there is a lack of studies in which the absolute concentration of 3-NT has been reported. Recent breakthrough technologies and modified analytical techniques have been reported to improve the selectivity and sensitivity of 3-NT detection. In this review, we have summarized the modifications to current analytical strategies and advancements in different approaches for 3-NT analysis. For the first time, pre-fabricated biosensors available for 3-NT have been reviewed in this article. A complete discussion on other advanced approaches such as capillary electrophoresis, electron paramagnetic resonance spectroscopy, and electron-vibration-vibration two-dimensional infrared spectroscopy for 3-NT analysis has been made. We have summarized the widest array of conventional and modern analytical techniques reported till date including the recent advancement in the field for the quantification of 3-NT in various types of biological samples.